Experimental opisthorchiasis: a study of blood cells, hematopoiesis and startle reflex in laboratory animals - D. F. Avgustinovich; I. A. Orlovskaya; L. B. Toporkova; G. B. Vishnivetskaya; A. V. Katokhin; M. N. Lvova; E. V. Kashina; N. P. Bondar; N. A. Feofanova; V. A. Mordvinov (Вавиловский журнал генетики и селекции)
One of the species of the family Opisthorchiidae, Opisthorchis felineus (O. felineus), causes severe disturbances in humans and animals, and so it is the subject of important research studies. Two weeks after infection we compared the impact of O. felineus invasion on the changes in blood cells composition, bone marrow hematopoiesis and behavioral startlereflex in inbred C57BL/6 male mice and Syrian hamsters (Mesocricetus auratus). Considerable interspecies differences were revealed for many parameters estimated. It was found that the relative weight of the main organ of the peripheral immune system – spleen, is significantly larger in mice than in hamsters. Moreover, the infection with O. felineus caused a significant enlargement of the spleen only in mice. More pronounced changes in the blood cells composition, which was accompanied by activation of hematopoietic stem cells of myeloid and erythroid set, were determined in hamsters. Blood changes in the response to infection in mice were less severe and were not accompanied by the changes in colony formation. Mouse acoustic startle reaction differed from hamster one too. The expression of the startle reaction and the value of pre-pulse inhibition were discriminated in animals of two species. Infected hamsters had no reaction of habituation  to the sound stimulus. In addition, the maturation of O. felineus worms was faster in hamsters than in mice. Data obtained suggest a greater resistance of mice to O. felineus infection, but do not exclude the availability of mice as a model in the study of processes taking place in the host during the development of experimental opisthorchiasis.